2013
DOI: 10.1111/ajps.12012
|View full text |Cite
|
Sign up to set email alerts
|

Economic Explanations for Opposition to Immigration: Distinguishing between Prevalence and Conditional Impact

Abstract: What explains variation in individuals' opposition to immigration? While scholars have consistently shown cultural concerns to be strong predictors of opposition, findings regarding the labor-market competition hypothesis are highly contested. To help understand these divergent results, we distinguish between the prevalence and conditional impact of determinants of immigration attitudes. Leveraging a targeted sampling strategy of high-technology counties, we conduct a study of Americans' attitudes toward H-1B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
244
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(255 citation statements)
references
References 65 publications
10
244
1
Order By: Relevance
“…They find that both low-skilled and high-skilled workers prefer high-skilled immigrants to low-skilled immigrants. Even more recently, Malhotra, Margalit, and Mo (2013) find persuasive evidence that job competition amongst hi-tech workers make natives much more likely to support restrictive immigration policy, again lending support to the idea that labor market competition matters.…”
Section: Pre-tax Labor Market Competitionmentioning
confidence: 94%
“…They find that both low-skilled and high-skilled workers prefer high-skilled immigrants to low-skilled immigrants. Even more recently, Malhotra, Margalit, and Mo (2013) find persuasive evidence that job competition amongst hi-tech workers make natives much more likely to support restrictive immigration policy, again lending support to the idea that labor market competition matters.…”
Section: Pre-tax Labor Market Competitionmentioning
confidence: 94%
“…Americans are divided in how they think about high-and low-skill immigrants, particularly in terms of their perceptions of the economic benefits and costs of these two immigrant groups (Hainmueller and Hiscox, 2010;Malhotra, Margolit, and Mo, 2013). We further disaggregate states' foreign-born population by skill levels to calibrate the size of the low-skill and high-skill immigration subpopulations.…”
Section: Newly Admitted Legal Permanent Residents (Lprs)mentioning
confidence: 99%
“…Comparative and cross-national research has shown that perceived cultural threat shapes attitudes toward immigrants regardless of where an immigrant is from or whether an immigrant is clearly of a different race/ethnicity than the majority of the native population (Hainmueller and Hiscox 2007;Malhotra et al 2013;Sniderman et al 2000). As such, the research to date indicates that cultural threats are important in shaping attitudes toward all immigrants and that the effect is not contingent on the presence of racial or ethnic differences.…”
Section: Original Articlementioning
confidence: 99%